OPTIMASI PENGGUNAAN ANTIMIKROBA BAGI PASIEN SEPSIS BERDASARKAN KARAKTERISTIK FARMAKOKINETIK DAN FARMAKODINAMIK OBAT: SEBUAH TINJAUAN LITERATUR - Titiesari, Yovita Diane; Febriani, Fany (Pengurus Pusat Ikatan Apoteker Indonesia, 2021)
Sepsis is one of a leading cause of death globally, and appropriate antimicrobial therapy is prominent to improve survival rate of septic patient. The pathophysiology of sepsis alongside with the use of therapeutic intervention such as renal replacement therapy could alter pharmacokinetic and pharmacodynamic profile of certain antimicrobials, thus will lead to subtherapeutic dose and treatment failure. This literature review will study the pharmacokinetic and pharmacodynamic profile of antimicrobials and its changes in septic patient and to apply this knowledge to optimise the dose of commonly used agents such as beta-lactams, vancomycin, aminoglycoside, fluoroquinolones, tigecycline, and antifungals, to improve patient’s safety